2019
DOI: 10.1002/mbo3.958
|View full text |Cite
|
Sign up to set email alerts
|

Combining culture and culture‐independent methods reveals new microbial composition of halitosis patients' tongue biofilm

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractBackground: Oral malodor is a very discomforting condition deriving from the presence of volatile sulfur compounds in the expired air. In halitosis of intraoral etiology, the volatile sulfur compounds are metabolic products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 43 publications
3
30
0
Order By: Relevance
“…Moreover, following the earlier findings, the researchers' results revealed the presence of Actinomyces odontolyticus, Solobacterium moorei, Prevotella melaninogenica, Fusobacterium periodonticum, and Tannerella forsythia in IOH patients. Furthermore, microorganisms such as Streptococcus parasanguinis, S. salivarius, Veillonella spp., and Rothia mucilaginosa dominated in the oral microbiota of healthy people [112].…”
Section: Chemical Compound Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, following the earlier findings, the researchers' results revealed the presence of Actinomyces odontolyticus, Solobacterium moorei, Prevotella melaninogenica, Fusobacterium periodonticum, and Tannerella forsythia in IOH patients. Furthermore, microorganisms such as Streptococcus parasanguinis, S. salivarius, Veillonella spp., and Rothia mucilaginosa dominated in the oral microbiota of healthy people [112].…”
Section: Chemical Compound Bacteriamentioning
confidence: 99%
“…The composition of the tongue microbiota has an essential influence on IOH. The most common molecular technique for testing and evaluating an oral cavity microbiome is the sequencing [5,107,112,113]. Seerangaiyan et al published a review in 2017, in which they showed the composition of the bacteria of Aggregatibacter, Campylobacter, Capnocytophaga, Clostridiales, Leptotrichia, Parvimonas, Peptostreptococcus, Peptococcus, Prevotella, Selenomonas, Dialister, Tannerella, and Treponema in the group of patients with IOH.…”
Section: Chemical Compound Bacteriamentioning
confidence: 99%
“…In addition, C. albicans and oral commensal streptococci have been shown to physically interact and display synergistic behavior within biofilms 30,41 , however, the impact of oral commensal streptococci in the S. mutans-C. albicans interaction is unclear. In this study, we demonstrate that S. parasanguinis, one of the most prominent commensals in the oral cavity 22,23 , interferes with S. mutans and C. albicans biofilm synergy in a H 2 O 2 and contact independent manner. Supporting this observation, CLSM analysis revealed a reduction in the size of S. mutans microcolonies in the presence of S. parasanguinis.…”
Section: Discussionmentioning
confidence: 64%
“…In this context, the tongue, with its distinct surface characteristics (fissures, crypts, papillae, saliva), could also be prone to the colonization, growth, and proliferation of microbiota [ 47 ]. It is a highly populated niche which has a significant impact on the colonization of other regions in the oral cavity [ 48 ] and could be a noninvasive biomarker for oral and systemic health [ 49 ]. Since it could be expected that colonization of the tongue by probiotics may have an impact on the microbiota and the health of the oral cavity, the fate of probiotics within tongue coatings should be considered in future clinical studies.…”
Section: Discussionmentioning
confidence: 99%